Gabon : 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2013)
Economic growth has been robust under favorable conditions in Gabon, but has not been inclusive enough, leaving one-third of its population in poverty. Building larger fiscal buffers, backed by a more prudent fiscal stance, will be critical to withstand possible negative oil price shocks. Efforts are under way to improve the management, and transparency of public finance must be carried out vigorously. Comprehensive policies are needed to support a diversified and more inclusive economic growth that is rich in employment opportunities.